KEPALA SEKOLAH SEBAGAI ADMINISTRATOR DALAM PENINGKATAN KOMPETENSI GURU SDN KARANG WARU KABUPATEN MUSI RAWAS UTARA - ANITA KURNIATI (IAIN Bengkulu, 2021)
This study describes the leadership of the principal in improving the competence of teachers in the Karang Waru Elementary School, Rupit District, Musi Rawas Utara Regency and the supporting and inhibiting factors of the principal's leadership in increasing the competence of teachers in the Karang Waru Elementary School, Rupit District, Musi Rawas Utara Regency In this study using field research (field research) with a descriptive approach. The results showed that the Principal of the Karang Waru State Elementary School, Rupit District, Musi Rawas Utara District has shown a real function and role in efforts to improve the competence of Islamic Religious Education teachers, such as providing guidance, motivation and appreciation to teachers and involving teachers in various training, workshops MGMP, KKG, UKG and PLPG and so on which are expected to position themselves as professional PAI teachers.To support school principals in improving PAI teacher competence, cooperation between teachers and school principals is needed, and discipline because discipline is instilled from an early age. by the principal to all school members, both the principal himself, teachers, students, and all staff, and the inhibiting factor is a problem in terms of infrastructure that is less supportive and in terms of students who do not get attention from parents so that when at school students are educated. is slow to follow.